13x-2(3x+6)=

Simple and best practice solution for 13x-2(3x+6)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13x-2(3x+6)= equation:


Simplifying
13x + -2(3x + 6) = 0

Reorder the terms:
13x + -2(6 + 3x) = 0
13x + (6 * -2 + 3x * -2) = 0
13x + (-12 + -6x) = 0

Reorder the terms:
-12 + 13x + -6x = 0

Combine like terms: 13x + -6x = 7x
-12 + 7x = 0

Solving
-12 + 7x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 7x = 0 + 12

Combine like terms: -12 + 12 = 0
0 + 7x = 0 + 12
7x = 0 + 12

Combine like terms: 0 + 12 = 12
7x = 12

Divide each side by '7'.
x = 1.714285714

Simplifying
x = 1.714285714

See similar equations:

| -8n+12=-4n-4 | | 2n^2+11n+10=0 | | r^2-8r-20=0 | | 7-7=18x+8x | | 3(x+8)=3x+12 | | x/2=-30+35 | | 3x+4x^2=56 | | -4+10=12x-5-11x | | 3(v-2)-5v=-2(v+2) | | 3(2x-5)=7(x+2) | | v^2+6v-7= | | -6(u+1)+8u=2(u-3) | | 5x+9x+2+x= | | -4+15=14-2-13x | | -3x=57 | | 2(x+2)=7x+4 | | -2v^2+8v+24= | | 6x^2-14x^2=0 | | (8x+12)=(5x+57) | | 4x+2(x+65)=36 | | 10x+2y=6 | | 11.3x=282.5 | | v^2+5v-6= | | 0.66x+0.83=3 | | 3x-18=30 | | C+11=-14 | | -5(3x-4)=2(x+27) | | 7x=-5 | | -(6y+1)-(-5y-8)=1 | | 27-3u^2= | | 2x+1=5x-6 | | M-2=-19 |

Equations solver categories